Design and Build Javanese Script Games for Elementary Schools using the Game Development Life Cycle Method - Aprylia; Prasetyo, Novian Adi (Nusantara Journal of Artificial Intelligence and Information Systems, 2025)
The Javanese script is a crucial part of Indonesia’s cultural heritage but is increasingly neglected by younger generations. This study aims to address the declining interest in learning the Javanese script by developing an educational game titled Susun Aksara Jawa for elementary school students in grades 3 to 6. The game was designed using the Game Development Life Cycle (GDLC) method and implemented through Construct 2, integrating gamification elements such as points, levels, badges, and progress tracking to enhance students’ motivation and engagement. The research process involved problem identification, literature review, data collection through pre-questionnaires, game design and development, functional testing using the Blackbox Testing method, and usability evaluation using the System Usability Scale (SUS). Fifteen students participated in user testing, resulting in an average SUS score of 71.5, categorized as “Good” (Grade C). The findings indicate that the integration of gamification effectively improves learning engagement and interest in the Javanese script among elementary students. This educational game demonstrates potential as an interactive and enjoyable alternative learning medium, contributing to the preservation and revitalization of regional language through educational technology.